2015
DOI: 10.1002/vnl.21531
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion property of crosslinked epoxidized (natural rubber)/(acrylonitrile‐butadiene) rubber blend adhesives in the presence of petro resin tackifier

Abstract: Loop tack, peel strength, shear strength, and morphology of (benzoyl peroxide)‐cured epoxidized natural rubber (ENR 25)/(acrylonitrile‐butadiene) rubber (NBR) blend adhesive were investigated by using petro resin as the tackifying resin. Benzoyl peroxide loading varied from 1 to 5 parts by weight per hundred parts of resin (phr), whereas the petro resin loading was fixed at 40 phr. A SHEEN hand coater was used to coat the adhesive on the polyethylene terephthalate substrate at 30 μm and 120 μm coating thicknes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 19 publications
2
2
0
Order By: Relevance
“…They reported three cases of benzene ring photo-oxidation: formation of benzyl acetophenone chromophores; acetophenone structures; and conjugated double bonds. The same observation was noticed in the irradiation of other substituted polystyrenes in solid films [25,26]. As can be seen from Figs.…”
Section: Ft-ir Spectra For Non-irradiated and Irradiated Pure And Blesupporting
confidence: 84%
See 3 more Smart Citations
“…They reported three cases of benzene ring photo-oxidation: formation of benzyl acetophenone chromophores; acetophenone structures; and conjugated double bonds. The same observation was noticed in the irradiation of other substituted polystyrenes in solid films [25,26]. As can be seen from Figs.…”
Section: Ft-ir Spectra For Non-irradiated and Irradiated Pure And Blesupporting
confidence: 84%
“…In an earlier study, it has been reported that irradiation of polystyrene solid films resulted in changes in many bands in the FT IR spectra [9], and also was noticed in the irradiated pure and blended poly (fluoro styrene) isomers with phthalate and terephthalate plasticizers in solid films [24,25]. The same observation was noticed in the irradiation of poly (4-vinyl biphenyl) solid films [41].…”
Section: Ft-ir Spectra For Non-irradiated and Irradiated Pure And Blesupporting
confidence: 57%
See 2 more Smart Citations